Enhancing Number Recognition Through Contextual Learning: A Classroom Action Research with Slow Learner Children in Kindergarten - Nurmulkiah, Fitri; Chamidah, Atien Nur (Journal of Innovation and Research in Primary Education, 2025)
Number recognition serves as a fundamental cornerstone for mathematical learning in early childhood, yet slow learner children face significant challenges in developing these essential skills. These children, representing approximately one-fifth of typical classrooms, demonstrate difficulties in information processing, weak short-term memory, and struggle with abstract concept formation, requiring specialized pedagogical approaches that connect mathematical concepts with concrete, meaningful experiences. This study investigated the effectiveness of contextual learning approaches in enhancing number recognition abilities among slow learner children in kindergarten settings. A Classroom Action Research design following Kemmis and McTaggart's cyclical model was employed over two cycles with six intervention sessions. Two slow learner participants aged 5-6 years from TK Negeri 1 Kec. Batu Ampar were selected based on their demonstrated difficulties in number recognition despite verbal counting abilities. Data collection utilized performance test checklists with 13 indicators across six competency areas, scored using a three-point scale. Contextual learning interventions incorporated familiar objects and daily life contexts, progressing from basic number cards to practical applications using shoes, clothing, and traditional games. Both participants achieved substantial improvements from baseline scores of 38-41% to final achievement rates of 76-80%, surpassing the 70% success criterion. The intervention successfully facilitated progression from "Belum Muncul" (Not Yet Emerged) to "Muncul" (Emerged) categories, demonstrating mastery of targeted number recognition skills. Contextual learning approaches effectively enhance number recognition abilities among slow learner children by transforming abstract numerical concepts into concrete, meaningful experiences, providing evidence-based guidance for inclusive early childhood mathematics education.